14-3-3 proteins inhibit autophagy by regulating SINAT-mediated proteolysis of ATG6 in Arabidopsis - Liu, Ting; Zheng, Yuping; Zhou, Shunkang; Wang, Yao; Lei, Xue; Xie, Lijuan; Lin, Qingqi; Chang, Changqing; Xiao, Shi; Qiu, Rongliang; Qi, Hua (BMC plant biology, 2024)
Autophagy is a conserved cellular process crucial for recycling cytoplasmic components and maintaining cellular homeostasis in eukaryotes. During autophagy, the formation of a protein complex involving AUTOPHAGY-RELATED PROTEIN 6 (ATG6) and phosphatidylinositol 3-kinase is pivotal for recruiting proteins involved in phagophore expansion. However, the intricate molecular mechanism regulating this protein complex in plants remains elusive. Here, we aimed to unravel the molecular regulation of autophagy dynamics in Arabidopsis thaliana by investigating the involvement of the scaffold proteins 14-3-3λ and 14-3-3κ in regulating the proteolysis of ATG6. Phenotypic analyses revealed that 14-3-3λ and 14-3-3κ overexpression lines exhibited increased sensitivity to nutrient starvation, premature leaf senescence, and a decrease in starvation-induced autophagic vesicles, resembling the phenotypes of autophagy-defective mutants, suggesting the potential roles of 14-3-3 proteins in regulating autophagy in plants. Furthermore, our investigation unveiled the involvement of 14-3-3λ and 14-3-3κ in the RING finger E3 ligase SINAT1-mediated ubiquitination and destabilization of ATG6 in vivo. We also observed repressed turnover of ATG6 and translocation of GFP-ATG6 to mCherry-ATG8a-labelled punctate structures in the autophagy-defective mutant, which suggesting that ATG6 is probably a target of autophagy. Additionally, 14-3-3λ and 14-3-3κ interacted with Tumor necrosis factor Receptor Associated Factor 1a (TRAF1a) to promote the stability of TRAF1a in vivo under nutrient-rich conditions, suggesting a feedback regulation of autophagy. These findings demonstrate that 14-3-3λ and 14-3-3κ serve as scaffold proteins to regulate autophagy by facilitating the SINAT1-mediated proteolysis of ATG6, involving both direct and indirect mechanisms, in plants. 14-3-3 proteins regulate autophagy by directly or indirectly binding to ATG6 and SINAT1 to promote ubiquitination and degradation of ATG6. 14-3-3 proteins are involved in modulating autophagy dynamics by facilitating SINAT1-mediated ubiquitination and degradation of ATG6.